2017
DOI: 10.1007/s13592-017-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the genetic content of Xylocopa frontalis bees (Apidae, Xylocopini) for sustainable management in pollination services of passion fruit

Abstract: The commercial use of pollinators can be beneficial to many crops. In the case of passion fruit, the supply of nests of Xylocopa frontalis in crop areas was shown to be effective for the improvement of the production and quality of fruits, but little is known about how the manipulation of native bees could change the genetic patrimony of local populations. The aim of this study was to describe the genetic composition of X. frontalis bees attracted to two agroecosystems, one natural reserve and one urban area b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
1
4
0
1
Order By: Relevance
“…This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015). Moreover, the gene flow between the two distinct groups (BCIN and CU) recognized in the haplotype network may be affected by Serra do Mar, a mountain range across the Atlantic rainforest in the coastal areas from Southeastern towards Southern Brazil (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 74%
“…This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015). Moreover, the gene flow between the two distinct groups (BCIN and CU) recognized in the haplotype network may be affected by Serra do Mar, a mountain range across the Atlantic rainforest in the coastal areas from Southeastern towards Southern Brazil (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 74%
“…Flowers that are animal-pollinated usually have larger showy petals of different sizes and shapes to attract pollinators. For example, study on two yellow melon hybrids showed that tropical hybrid has larger flowers that could be more attractive to bee species such as A. mellifera, [57] large solitary bees of genus Xylocopa by providing larger landing platform [58,59] compared to the other melon hybrids from Brazil. There is a positive connection between the size of flowers, inflorescences, or flower fields and attractiveness to insects.…”
Section: Shape and Sizementioning
confidence: 99%
“…The population structuring was also investigated by performing a Bayesian clustering algorithm imbedded in Structure, version 2.3.4 (Pritchard et al 2000). The number of best-fitting populations (K) was explored using the admixture model, which was set with a configuration of 100 000 cycles and 500 000 repetitions (as described by Toledo et al 2017) of the Markov chain Monte Carlo. K-values ranged from 1 to 6 and were repeated 10 times.…”
Section: Microsatellite (Simple Sequence Repeat) Analysismentioning
confidence: 99%
“…The geographic-distance matrices were calculated from the minimum distance of different groups among the sampling sites (Supplementary material, Table S1). Genetic distances were generated using pairwise F ST values, as described in Zayed and Packer (2007) and Toledo et al (2017). In all analyses, only P-values < 0.05 were considered significant.…”
Section: Microsatellite (Simple Sequence Repeat) Analysismentioning
confidence: 99%